2020
DOI: 10.1111/jdv.16559
|View full text |Cite
|
Sign up to set email alerts
|

Non‐invasive clinical and microscopic evaluation of the response to treatment with clobetasol cream vs. calcipotriol/betamethasone dipropionate foam in mild to moderate plaque psoriasis: an investigator‐initiated, phase IV, unicentric, open, randomized clinical trial

Abstract: Background Treatment response for psoriasis is typically evaluated using clinical scores. However, patients can relapse after clinical clearance, suggesting persistent inflammation. Dermoscopy, reflectance confocal microscopy (RCM) and optical coherence tomography (OCT) can non-invasively improve treatment response assessment. Objectives To compare the clinical and non-invasive microscopic features in a psoriatic target lesion treated with clobetasol cream or calcipotriol/betamethasone dipropionate foam (Cal/B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…We observed a good correlation between ET and TSS. Our results on the decrease of ET under therapy were in good agreement with previous studies using topical ( 25 , 40 ) and non-biologic systemic therapies ( 19 ). In contrast to conventional therapies of psoriasis, we observed an accelerated decrease of ET .…”
Section: Discussionsupporting
confidence: 92%
“…We observed a good correlation between ET and TSS. Our results on the decrease of ET under therapy were in good agreement with previous studies using topical ( 25 , 40 ) and non-biologic systemic therapies ( 19 ). In contrast to conventional therapies of psoriasis, we observed an accelerated decrease of ET .…”
Section: Discussionsupporting
confidence: 92%
“…9 Cal/BD foam has also shown superior efficacy to its individual components, calcipotriol and betamethasone dipropionate, Cal/BD gel and ointment formulations as well as clobetasol cream. [11][12][13][14] In one study, the percentage of patients achieving treatment success after 4 weeks, defined by a PGA score is higher in the Cal/BD foam group than in the Cal/BD ointment group (54.6% vs 43%). 13 In a second study, 52.1% of patients receiving Cal/BD foam achieved PASI75 after 4 weeks, compared with 24.3% receiving Cal/BD gel.…”
Section: Short Term Efficacymentioning
confidence: 99%
“…12 Cal/BD foam has also demonstrated superior effectiveness to clobetasol cream, along with higher levels of patient satisfaction. 14 In a recent interventional investigator-initiated Phase IV study, more patients treated with Cal/BD foam achieved a total clinical score of 1 or less, indicating better clinical resolution than with clobetasol. 14 Cal/BD foam induced a significantly faster response than clobetasol, with 80% of patients achieving a meaningful reduction in total clinical score, versus 43.4% at 4 weeks.…”
Section: Short Term Efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a prospective, open‐label, study ( N = 36) found that Cal/BD foam treatment resulted in a significantly higher number of patients achieving total or almost total lesion clearance (TCS ≤ 1) after 4 weeks compared with clobetasol cream (63.2% vs. 18.8%, respectively; P = 0.016) 11 . In addition, Cal/BD foam induced a faster and greater reduction of epidermal thickness ( P < 0.049) and patients' treatment satisfaction was higher ( P < 0.03).…”
Section: Efficacymentioning
confidence: 99%